2019
DOI: 10.3386/w25664
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Formation in Legislative Bargaining

Abstract: , and the 2019 Barcelona Summer Forum for useful comments and discussions. Aviv Caspi and Neelanjan Datta provided outstanding research assistance. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Let g i,l and g i,j be the links chosen by agent i with agents l and j. Agent i chooses the links solving (7) under the constraint that g i,j ∈ [0, g] for all j ∈ N . It is easy to see that, given (E j (G, ε)) j∈N , problem (7) is concave in g = (g i,1 , ..., g i,n ) and, therefore, it has a unique solution whose necessary and sufficient condition is: g * i,j ≤ (θ i,j ) 1+φ αδE * j φ , satisfied as an equality in an interior solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Let g i,l and g i,j be the links chosen by agent i with agents l and j. Agent i chooses the links solving (7) under the constraint that g i,j ∈ [0, g] for all j ∈ N . It is easy to see that, given (E j (G, ε)) j∈N , problem (7) is concave in g = (g i,1 , ..., g i,n ) and, therefore, it has a unique solution whose necessary and sufficient condition is: g * i,j ≤ (θ i,j ) 1+φ αδE * j φ , satisfied as an equality in an interior solution.…”
Section: Discussionmentioning
confidence: 99%
“…Related literature As we discussed above, legislative activity typically is modelled as a bargaining protocol in the political economy literature. The classic reference is Baron and Ferejohn [1989], while alternative bargaining protocols have been presented by Austen-Smith and Banks [1988], Morelli [1999], Baron and Diermeier [2001], Seidmann et al [2007], Battaglini [2019], and others. In these works, there is little space for the legislators' social connections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, Banks and Duggan (2006) show that in a general version of the Baron Ferejohn model, equilibria will have no delay. 9 On the other hand, several papers have shown that inefficiencies arise when the allocation of power changes over time because of voters behavior (Battaglini and Coate (2008)), when present actions have effects on future available actions (Acemoglu, Egorov, and Sonin (2008)), when players disagree on what to do given the evolving environment (Dziuda and Loeper (2016)), when an agent can act as an intermediary in legislative bargaining (Iaryczower and Oliveros (2016)), or because coalition principals face a trade-off between efficiency and surplus extraction (Battaglini (2019)). We contribute to this literature by highlighting a novel dynamic effect that changes willingness to trade of all players.…”
Section: Related Literaturementioning
confidence: 99%